2014
DOI: 10.4236/jwarp.2014.611099
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Wash Bay Effluent on the Water Quality of a Subtropical River

Abstract: Washbay effluents have received scant attention as a potential source of water pollution globally. This study is the first to investigate the potential impact of the total wash bay effluent content released into river water in Africa. We investigated the potential ramifications of wash bay effluxent released off Charter Estates, Chimanimani in the Eastern Highlands of Zimbabwe on the water quality of the receiving subtropical Nyahode River by measuring selected water limnochemical aspects which included biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
8
1
Order By: Relevance
“…The downside of in vivo toxicity bioassays is that they give limited information about the substance or substances responsible for an observed effect. However, looking at Table 3 Exceptionally high BOD concentrations (range 114-650 mg/l) were observed in five of the effluent samples, with only CW6 (27 mg/l) complying with the WHO guideline value of 30 mg/l (Danha et al 2014). While this observation has partly been attributed to the presence of LAS in effluent samples, high BOD is also an index of organic pollution in a water matrix (Adedolapo and Olajumoke 2012).…”
Section: Figure 3: Concentrations Of Heavy Metals In Carwash Effluentsmentioning
confidence: 99%
“…The downside of in vivo toxicity bioassays is that they give limited information about the substance or substances responsible for an observed effect. However, looking at Table 3 Exceptionally high BOD concentrations (range 114-650 mg/l) were observed in five of the effluent samples, with only CW6 (27 mg/l) complying with the WHO guideline value of 30 mg/l (Danha et al 2014). While this observation has partly been attributed to the presence of LAS in effluent samples, high BOD is also an index of organic pollution in a water matrix (Adedolapo and Olajumoke 2012).…”
Section: Figure 3: Concentrations Of Heavy Metals In Carwash Effluentsmentioning
confidence: 99%
“…The effect of the effluent as recorded in the higher mean values of major ions (phosphate, sulphate, and nitrate) has been reported by researchers such as Sablayrolles et al (2010) [25], Aisling et al (2011) [26], Adeyemi-Ale (2014) [27], and Danha et al (2014) [12]. They attributed the increase in loads of these major ions to the hydrocarbon components of detergents being used at the carwash bay, thus to organic pollution.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, detergent wastes can have poisonous effects on all types of aquatic life if they get accumulated in sufficient quantities [11]. Detergents could also affect receiving aquatic environments by causing foaming and eutrophication, therefore limiting oxygen production [12]. The hazard of detergent pollution also lies in their effect on water ecosystems as a whole for surfactants may adversely affect microalgae at the lowest trophic level, impacting their function as major suppliers of oxygen to water bodies and result in community structure infringement [13].…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively higher concentrations of variables related to vehicle washing were detected at the impact sites (Table 3). Other studies have also reported impact of VWW on surface water chemistry with maximum deterioration at the VWW discharge zones (Chukwu, Segi, & Adeoye, 2008;Danha et al, 2014). Paired-samples t test (Table 4) also indicated significant impact of influxed VWW in certain water quality variables.…”
Section: Physico-chemical Variables Of Surface Watermentioning
confidence: 68%
“…Discharge of such contaminants into the surface water bodies degrade water quality which in turn affectaquatic ecosystems and also impair the use of water for household, industrial, agricultural, and recreational purposes. The surface water pollution due to untreated VWW has been mostly reported from developing countries like Ghana (Aikins & Boakye, 2015), India (Mazumber & Mukherjee, 2011), Pakistan (Yasin, Iqbal, Arshad, Rustam, & Zafar, 2012), and Zimbabwe (Danha, Utete, Soropa, & Rufasha, 2014). Corresponding to these studies, Sato, Qadir, Yamamoto, Endo, and Zahoor (2013) have also reported that in low-income countries, only 8% of industrial and municipal wastewaters are treated.…”
Section: Introductionmentioning
confidence: 99%